Experimental Implementation of a Windshield Warning System on an Actual Vehicle - Chyi-Yeu LIN; Jinn-Feng JIANG; Yi-Jie CHEN; Hung-Yuan WEI; Cheng-Hsien WANG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
A windshield warning system for vehicles is presented. The system assists drivers in identifying potential hazardous object without the need to divert attention from the road. The target is identified by the camera and the software system and then used to construct the line-of-sight equation based on the coordinate system of the moving vehicle. The explicit equation of the intersection point of the line of sight and the windshield surface is derived using an algebraic method. A warning mark is then projected at the intersection point on the windshield by a two-degree-of-freedom laser projector, allowing the driver to easily identify the obstacle. The feasibility of the proposed system was verified using an actual vehicle (Luxgen® 7 MPV).